Need For Long-Term Care in Children is Increasingly Caused by Disorders of Psychological Development. Changes in the Care Causing Diagnoses According to German Social Code (SGB XI) Between 2009–2014 - Beck-Ripp, Julia Christiane; Dressel, Holger (Das Gesundheitswesen, 2019)
Aim of the study There is an ongoing discussion on the increasing number of children with mental and developmental disorders, with some even needing long-term care according to the German Social Code XI. This study was performed to identify the main diagnoses justifying such care in children and to analyse their prevalence over time.Methods The diagnoses justifying long-term care were evaluated using care assessments of Bavarian children and adolescents between 2009 to 2014 by the medical service of statutory health insurance.Results Over the years investigated, the percentage of assessments due to a mental and behavioural disorder rose significantly from 36.2 to 42.2%. Since 2012, the most common diagnose changed from Down's syndrome to pervasive developmental disorders with marked increase of also mixed specific developmental disorders. In new applications for nursing insurance services the proportion of pervasive developmental disorders rose gradually from 151 in 2010 to 254 in 2014. During the whole period of time, the overall care dependency in children seemed to be stable.Conclusions These observations might rather be influenced by altered awareness of health and illness, increasing readiness to seek help with psychological or developmental impairments as well as changed diagnostic criteria than by a steady increase in affected individuals.
Keywords: long-term care; children; adolescents; autism spectrum disorders; psychological developmental disorders